Pemanfaatan Buah Mangrove Menjadi Prodak Makanan Di Desa Hurip Jaya Bekasi - Handayani handayani; Yasser Ahmed (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2022)
Mangrove forest is the main ecosystem supporting the life of coastal communities. In addition to having an ecological function as a food provider for marine life, coastal abrasion barrier, tidal wave and tsunami barrier, waste absorber, preventing sea water intrusion, mangrove forests can also serve to provide food needs for the surrounding population. The potential of mangrove fruit can be processed into food and drinks that can increase the welfare of the people who have only depended on marine products for their lives. The objectives of community service are (1) educating the public about the types of mangrove fruit, (2) identification of mangrove fruit, the benefits of mangroves for the environment and society; (3) Practicing the processing of mangrove fruit into food and beverages (syrup, jam and candy). This community service is carried out using the lecture method and practicing how to process mangrove fruit into syrup, candy and jam then documented in the form of photos and videos stored on a compact disk (CD). Participants in community service were attended by 25 mothers and teenagers. The results of this service activity show that residents are very interested in processing various foods and drinks made from mangrove fruit. This can be seen from the results of the questionnaire, that the increase in participants' knowledge increased by 100% after the training showed that the community understood the benefits of mangroves for the environment and the community and were interested in practicing making syrup, jam and candy from mangrove fruit